2010
DOI: 10.1177/0042085910377859
|View full text |Cite
|
Sign up to set email alerts
|

A Charter School’s Journey Toward Serving All Learners: A Case Study

Abstract: Public charter schools across the country are struggling to better serve a range of students with disabilities. Using the approach of a participatory evaluation, a K-8 college preparatory school community of teachers, administrators, parents, and students were better able to define those practices that impeded or supported a high-quality proactive integrated comprehensive service delivery model for all learners. In so doing, they were empowered to take their research findings and move to action through adaptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…The school activities including the breakfast program, after school tutorial program, and student resource center are provisions established to motivate students. This revelation supports a recent study by Drame and Frattura (2011); they indicated that when school practices support high school expectations with dedicated and committed teachers; the students will succeed. This finding concludes on the premise that motivation does impact student performance.…”
Section: On the Second Central Research Question; How Is Motivation Csupporting
confidence: 87%
“…The school activities including the breakfast program, after school tutorial program, and student resource center are provisions established to motivate students. This revelation supports a recent study by Drame and Frattura (2011); they indicated that when school practices support high school expectations with dedicated and committed teachers; the students will succeed. This finding concludes on the premise that motivation does impact student performance.…”
Section: On the Second Central Research Question; How Is Motivation Csupporting
confidence: 87%
“…The outcomes of these processes are reflected in relative levels of race and class segregation between charter schools and other public schools (Renzulli, 2006; Renzulli & Evans, 2005; Saporito & Sohoni, 2007). Moreover, disparities have been identified between charter schools and other public schools related to the provision of curriculum and services tailored to special needs students by charter schools (Drame & Frattura, 2011; Estes, 2006).…”
Section: Methods and Datamentioning
confidence: 99%
“…The shortcomings and contradictions inherent in the charter school model become apparent when areas such as special education are examined. Estes (2006), and Drame and Frattura (2011) identified difficulties that charter schools confront when attempting to design curriculum for students with learning disabilities and behavioral disorders. Although charter schools are public and obligated to accommodate all students, some did not have adequate staff or resources to provide curriculum and services tailored to special needs students in a manner comparable to other public schools.…”
Section: Disincentives To Serve the Needs Of Troubled Studentsmentioning
confidence: 99%
“…This leads to resource desynchronizing, consultation loss, diffuse and passive teacher role, and delayed and less effective interventions. This can also be associated with research showing (a) insufficient teacher involvement or participation in the process (Meyers et al, 1996; Robinson, 2002; Slonski-Fowler & Truscott, 2004), as well as (b) teachers’ perceptions of having limited skills and preparation for working with challenging students (Drame & Frattura, 2011).…”
Section: Discussionmentioning
confidence: 99%